Lost, dysfunctional or evolving? A view of business schools from Silicon Valley - Kyle Eischen; Nirvikar Singh (University of California, Economics Department, 2005)
Recent articles have rekindled discussions around the direction and relevance of US business schools. The two main viewpoints are distinct but equally critical. On one hand, business schools are considered overly focused on scientific research and having lost their connection to real world and management issues. On the other hand, schools are considered dysfunctionally focused on media rankings and short-term superficial marketing fixes. Our study of educational opportunities and workforce development in Silicon Valley suggests a different viewpoint. We agree that both approaches correctly identify the challenge of preparing managers in globalized world. However, we believe they misdiagnose the cause of the failure. Rather than being lost or dysfunctional, we believe business programs - like the firms and students they serve - are in the process of evolving to meet a shifting global and local environment. Our findings indicate that business schools face structural, content, and program shifts. Educationally, business programs continue to be seen as doing a good job of educating their students in core functional areas and processes. However, they do less well in teaching their graduates interpersonal skills, real-time decision-making, recognition of contexts, and integration across functional areas. These are increasingly the skills demanded by the global business environment. Even more challenging is meeting the demand for both sets of skills within very specialized fields like technology management. Structurally, new types of students and learning demands are placing stresses on traditional full-time two-year programs and their business models. Women and minority groups increasingly form the majority of the future student population, with distinct needs and demands for part-time and executive education. This shift is also evident in demands for life-long learning and engagement as opposed to a fixed, one-shot program experiences. These challenges require business schools to build upon what they do well, while innovating to serve new business and student needs.
Keywords: I23; M00; L80; R11; 330; management education; Silicon Valley; globalization; technology; Wirtschaftshochschule; Wirtschaftsstudium; Anforderungsprofil; Silicon Valley; USA; IKT-Sektor